Compressibilidade do solo e pressão de pré-consolidação: determinação, predição e interações - Tassinari, Diego (2019)
The study of soil mechanical behavior is of great relevance in the assessment of soil compaction on agricultural systems. Most commonly, mechanical strength is evaluated from the soil compressive behavior, determined by the soil compression curve derived from uniaxial compression tests. The soil property most often associated to mechanical strength is the precompression stress (σ p ), considered an indicator of the soil load-bearing capacity. The present study aimed to assess the soil changes that take place during compression (article 1), compare different methods for determining σ p from soil compression curves (article 2), and to verify how σp may be predicted from other attributes (article 3). During compression, soil samples were subjected to both compaction and consolidation, the latter majorly related to the water tension (Ψ) of 10 kPa and higher applied loads. The compaction degree observed throughout the role applied pressure range was strongly dependent on the soil initial condition. The shape of the compression curve, whether bi-linear or sigmoid, was significantly affected by Ψ a by the sample’s initial condition. The method for determining σp and the soil attribute used for representing the compression curve interact to each other. Besides the nonlinear relation between bulk density and void ratio, method performance was also affected by the relation between the physical attribute and the applied pressure during compression, whether direct or inverse. Determination of σ p from the intersection of two linear models (defined by the first and the last three points of the soil compression curve) proved to be a viable and reliable choice. Prediction of σ p becomes more accurate when relative measures, such as the degree of compaction, are employed in the models, what reduces the effect of varying intrinsic attributes, like soil texture.